1999
DOI: 10.1016/s0008-6363(98)00336-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic changes in rat and guinea pig coronary microvascular endothelium after culture: loss of nitric oxide synthase activity

Abstract: These data demonstrate that freshly isolated rat and guinea pig CMVEs possess ecNOS activity, and that this activity is downregulated following culture. At least for the rat, this effect would seem to lie at both the transcriptional and translational level. Furthermore, rat CMVEs have reduced activity of sGC following culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…On the other hand, it is well known that working with endothelial cells at higher passages may be artifact-prone because they hardly produce any NO. 50 In addition, it is important to distinguish between shear stress and (cyclic) stretch which per se are very different biomechanical forces both in terms of direction (unidirectional versus bidirectional deformation) and relative strength (typically stretch is 3 to 4 orders of magnitude greater than shear stress).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is well known that working with endothelial cells at higher passages may be artifact-prone because they hardly produce any NO. 50 In addition, it is important to distinguish between shear stress and (cyclic) stretch which per se are very different biomechanical forces both in terms of direction (unidirectional versus bidirectional deformation) and relative strength (typically stretch is 3 to 4 orders of magnitude greater than shear stress).…”
Section: Discussionmentioning
confidence: 99%
“…Because our analysis of cAMP dynamics after combined selective inhibition of PDE3 and PDE4 activities in HUVECs and HMVECs had shown that these treatments resulted in an approximately additive effect on cAMP levels, we had initially predicted that dual PDE3 and PDE4 inhibition would have similarly affected migration in an additive manner. Although a possible explanation for the apparent antagonistic effect of combined PDE3 and PDE4 inhibition on migration of these cells may stem from the impact of VEGF-induced increases in cGMP (Ferrara, 1999;Lang et al, 1999;Wohlfart et al, 1999; Rivero- Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was therefore designed to investigate the reciprocal relationship between coronary endothelial cell growth and the concurrent expression and activity of the enzymes, namely, eNOS and NAD(P)H oxidase that are associated with the regulation of endothelial cell redox state. All the experiments outlined in the current study were carried out using early-passage cultured rat CMEC in order to avoid the effects of changes in coronary endothelial cell phenotype on enzyme expression and activity [30]. Significant increases in eNOS mRNA and protein expressions, eNOS activity and consequently in nitrite generation, the ultimate breakdown product of NO, were observed in proliferating versus confluent CMEC.…”
Section: Discussionmentioning
confidence: 99%